Estudo das técnicas de GD&T e sua aplicação em máquinas de medição por coordenadas - Quirino, Julyana Maria de Medeiros (2017)
Geometric Dimensioning and Tolerancing is a tool that aims to communicate project specifications unequivocally. In contrast to the traditional Cartesian system of dimensioning and tolerancing, this tool considers the geometric characteristics of the features to establish the tolerance zones and does not only evaluate the dimensional compliance of a part. In addition, GD&T does not only question the quality of the manufactured part, but also the quality of the design used to produce the part. The associated use of GD&T and coordinate measuring machines allows performing geometric tolerance analysis effectively and automatically, generating economic and technical benefits due the standardization of inspection processes. This dissertation discusses the application of GD&T techniques in a CNC coordinate measuring machine. A bibliographic review of the use of these techniques is also presented. Two aluminum parts produced in a machining center were characterized geometrically through the geometric tolerance analysis tools available in the native software of the machine, according to the position, roundness, perpendicularity, parallelism and angularity of parts elements.